2012
DOI: 10.1371/journal.pone.0048328
|View full text |Cite
|
Sign up to set email alerts
|

Is Wetter Better? An Evaluation of Over-the-Counter Personal Lubricants for Safety and Anti-HIV-1 Activity

Abstract: Because lubricants may decrease trauma during coitus, it is hypothesized that they could aid in the prevention of HIV acquisition. Therefore, safety and anti-HIV-1 activity of over-the-counter (OTC) aqueous- (n = 10), lipid- (n = 2), and silicone-based (n = 2) products were tested. The rheological properties of the lipid-based lubricants precluded testing with the exception of explant safety testing. Six aqueous-based gels were hyperosmolar, two were nearly iso-osmolar, and two were hypo-osmolar. Evaluation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
84
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(93 citation statements)
references
References 62 publications
5
84
0
2
Order By: Relevance
“…However, clinical evaluation of N-9 was stopped due to increased HIV incidence in women using an N-9 vaginal gel (3). Additionally, N-9 was shown to cause tight junction disruptions in epithelial cells in vitro (4) and to be harmful to beneficial vaginal flora (5). Other candidates, such as BufferGel (6), the carrageenan derivative Carraguard (7), and polyanionic gels (PRO 2000 [6] and cellulose sulfate [4]), were all unsuccessful as HIV microbicides.…”
mentioning
confidence: 99%
“…However, clinical evaluation of N-9 was stopped due to increased HIV incidence in women using an N-9 vaginal gel (3). Additionally, N-9 was shown to cause tight junction disruptions in epithelial cells in vitro (4) and to be harmful to beneficial vaginal flora (5). Other candidates, such as BufferGel (6), the carrageenan derivative Carraguard (7), and polyanionic gels (PRO 2000 [6] and cellulose sulfate [4]), were all unsuccessful as HIV microbicides.…”
mentioning
confidence: 99%
“…Moreover, onset of uptake 543 was rapid since no noticeable differences were observed between 544 incubation times from 30 min to 4 h (data not shown). for vaginal HIV prevention [56,57]. In this study, different epithe-555 lial and one macrophage cell lines were used for studying the abil-556 ity of NPs to modulate the toxicity of dapivirine.…”
mentioning
confidence: 99%
“…8,28,29 Although identified as generally-regarded-as-safe excipients by the Food and Drug Administration (FDA), several of these excipients were reported to affect the epithelial barrier in human cell culture or animal models. [18][19][20][21] Excipients chosen for evaluation represent a variety of functional categories and diverse chemical structures. The excipient concentration used in this study (Table 2) was determined based on the following considerations: Disodium EDTA is widely reported to decrease the integrity of intestinal cell monolayer (Caco-2) 30 and excised intestinal epithelium, 31 so three concentrations (0.05%, 0.1%, and 1%) were chosen to cover the relevant levels of use.…”
Section: Selection Of Excipients and Determination Of Experimental Comentioning
confidence: 99%
“…Some hyperosmolar over-the-counter lubricant gels have been found to reduce the tissue viability and to result in epithelial fracture/sloughing in an ectocervical explant model. 18 Several other tissue explant and mouse studies reported that treatment with excipients that are frequently used in vaginal products could alter the cervicovaginal tissue integrity and even increase the rate of vaginal herpes simplex virus 2 (HSV-2) transmission. [19][20][21] McClelland et al evaluated the effect of vaginal washing on the incidence of HIV-1 infection in 1,270 African women between 1993 and 2003.…”
mentioning
confidence: 99%